THE ROLE OF MOTIVATION IN LEARNING ENGLISH AS A FOREIGN LANGUAGE (Ustozlar uchun, 2026)
Motivation is one of the most significant factors affecting the success of foreign language learning. It influences students’ willingness to participate in classroom activities, complete learning tasks, and achieve language proficiency. This article examines the importance of motivation in learning English as a foreign language, discusses different types of motivation, and analyzes their impact on students’ academic achievement. The paper also highlights effective strategies teachers can use to enhance learners’ motivation and improve language learning outcomes.